Improving Academic Writing Skills through Artificial Intelligence-Based Training - Retno Lestari; Heni Dwi Windarwati; Yati Sri Hayati; Marcellina Tiarani Putri; Jennifer Aishah Ratu Bernardy; Juwita Nindya Kartika (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: The integration of artificial intelligence (AI) into academic environments has been on the rise to enhance research productivity and improve the quality of academic writing. Despite the growing interest in this area, empirical evidence on the measurable impact of AI-based training on academic writing skills remains limited. The aim of this community service activity was to enhance the participants' academic writing skills through a structured AI-assisted training program. Methods:  This community service program was conducted over a three-day period in May 2025 at the Faculty of Health Sciences, Universitas Brawijaya, Indonesia. A total of 30 university students volunteered to participate in this study. The community service program comprised five stages: preparation, socialization, training implementation, and evaluation. The training methods included socialization, counseling, workshops, and hands-on practicums focusing on AI-based academic writing. The evaluation was executed employing a pretest–posttest design, in which a writing rubric was used to assess the participants’ academic writing skills. Results: The analysis indicated a significant improvement in writing performance following the AI-based training. The mean pretest score was recorded at 65.3 (SD = 7.5), while the posttest mean reached 81.2 (SD = 6.8). The paired-sample t-test highlighted a statistically significant difference between the pretest and posttest scores (t = 8.24, df = 29, p < 0.001). Conclusion: The AI-based academic writing training implemented through this community service program effectively enhanced the participants’ writing skills. This program demonstrates that AI-assisted training can be an effective model for strengthening academic writing competence in community service initiatives.